From Waste to Eggs: A Circular Economy Model for the Economic Resilience of Fishermen in Pegantungan Village - Falin Atsal, Naufalin Atsal Fadhila (Prospect Publishing, 2025)
The fishing community in Pegantungan Village faces significant challenges, including income instability due to seasonal dependency and severe environmental pollution from unprocessed crab shell waste. This situation is compounded by the limited economic roles available to women. This article discusses a community empowerment initiative, the Pegantungan Sejahtera program, which was designed to address these interconnected issues through an integrated approach. The program's objective is to build economic resilience and environmental sustainability. The method utilizes circular economy principles and an Asset-Based Community Development (ABCD) framework, empowering the community through training and mentoring to transform crab shell waste into high-nutrient feed for a poultry farming enterprise. The results show that this model has been highly effective. It has successfully reduced a substantial amount of local waste, lowered livestock operational costs, and established a new, consistent income stream for participating families. This initiative demonstrates a replicable solution for turning environmental liabilities into economic assets, fostering greater community self-sufficiency.